Developing Intercultural Language Materials - Mishan, Freda (Routledge Taylor & Francis Group, 2024)
Developing Intercultural Language Materials puts intercultural competence at the forefront of the learning agenda. It unpicks its underlying theory and provides a framework and practical methodologies for practitioners, providing a toolkit for them to create their own learning materials and design their own classroom activities to nurture intercultural competence.This innovative book showcases some of the new ways language teachers in practice successfully integrate this essential skill into their curricula. Directions for further research, pulling out recurring threads in this book, such as critical pedagogy and cultural sensibility, offer opportunities for professional development.This research-grounded and action-oriented text is essential reading for language and cultural studies practitioners who want to help their students thrive in today's multicultural world.